The potential of cassava-goat integration in aerial and fertilizer production in Lampung - Anhar Faisal Fanani; Asnath Maria Fuah; I Komang Gede Wiryawan; Salundik Salundik; Nurul Fajrih; Suhardi Suhardi; Ari Wibowo; Rohmatul Anwar (Politeknik Negeri Jember, 2023)
This study aimed to evaluate the integration potential of cassava plants with goats in aerial production and goat manure-derived fertilizers. This research was conducted by purposive sampling with the consideration that Lampung Province is the central region of cassava production in Indonesia and is the region with the highest population of goats outside Java Island. Sampling was carried out in Central Lampung and East Lampung with high-production cassava and goats. Analysis using LQ, FPCI, carrying capacity, and fertilizer production from goat manure. The data obtained was then presented descriptively. The results showed that FPCI was located in Central Lampung, East Lampung, North Lampung, Tulang Bawang, and Tulang Bawang West. The highest aerial carrying capacity of cassava, 31.6%, was concentrated in Central Lampung, thereby affecting the livestock carrying capacity. LQ analysis obtained showed that around 66.7% of the area in Lampung was a goat livestock base. The highest production of fertilizer from goat manure was obtained by South Lampung, which covers around 24.5% of the total area of Lampung. The conclusion from this study was that areas that have potential for development supported by the provision of feed sourced from aerial sources from cassava plant waste if integrating cassava plants and goat livestock were East Lampung, Central Lampung, North Lampung, Tulang Bawang, and Tulang Bawang Barat districts.